Case report of atypical endometrial stromal cells in an endometrial polyp and osteoclastic like giant cells in leiomyoma in the same patient: Is it a coincidence or is it a result of Tamoxifen treatment? - Öztürk, Çiğdem; Çay, Tuğçe; Tetikkurt, Seza; Kasımogullar, Emre Volkan; Karacan, Tolga (Acta Biomedica Atenei Parmensis, 2019)
Atypical stromal cells are rarely identified in the endometrial polyps of the female lower genital system. These cells are suggested to develop due to a degenerative or reactive phenomenon. And osteoclastic like giant cells, which have been reported in many epithelial and mesenchymal tumors of uterus, may develop because of a degenerative or a reactive process. In this case report, we present a breast cancer patient who was commenced on Tamoxifen treatment presenting with formation of both atypical stromal cells in an endometrial polyp and osteoclastic like giant cells in the leiomyoma of the uterus. Patients who are treated with Tamoxifen should be followed meticulously to detect tumoral or proliferative lesions of endometrium and myometrium because of the adverse effects of tamoxifen on uterus. (www.actabiomedica.it)